A domain–specific language for Virtual Classrooms. (27th October 2014) - Gañán, David; Guerrero–Roldán, Ana–Elena; Prieto–Blázquez, Josep; Conesa, Jordi
This paper proposes the creation of a model–driven development approach on top of a Virtual Learning Environment (VLE) in order to automate the process of creating Virtual Classrooms. In particular, a Domain–Specific Language (DSL) has been defined for the creation of Virtual Classrooms reusing a specific ontology for Virtual Classrooms. The DSL has been validated in a real case study: the creation of Virtual Laboratories at the Open University of Catalonia. The validation has shown that the approach enhances the reusability of Virtual Classrooms for the upcoming courses and the DSL allows describing Virtual Classrooms graphically at a high abstraction level. In addition, classrooms can be easily modified and automatically exported to other learning systems like Moodle.